Sierra South : backcountry trips in California's Sierra Nevada - Wenk, Elizabeth; White, Michael C., 1952- (Sierra Nevada guides, 2021)
The rush of trekking through nature, the thrill of experiencing new places, the reward of discovering beautiful sights--all of this awaits in the Sierra Nevada. For more than 40 years, this definitive guidebook has led readers along the top trails between Tehachapi Pass and the southern border of Yosemite National Park. Now, with the revised and updated edition, let hiking experts Elizabeth Wenk and Mike White show you the way. Sierra South features 80 meticulously selected trips, from new routes to old favorites. Traverse the stunning wilderness areas and national forests of the region, including Kings Canyon National Park, Sequoia National Park, John Muir Wilderness, Ansel Adams Wilderness, and many more. The trips are organized around major highways and roads, so it's easy to choose your next adventure. Just pick an area, drive there, and go hiking. Inside you'll find: 84 trips that range from quick overnighters to 12-day excursions; complete trip details, including day-by-day trail descriptions, GPS waypoints, and elevation data; 41 trailhead maps that show the routes for every trip; beginner tips and trusted advice on camping, fishing, and bear safety; information on side trips, geology, natural history, and more. Planning your trip into the southern Sierra backcountry is easier than ever before. For additional hiking and backpacking opportunities, see the companion guide Sierra North.